EXPERIENCE OF USING MECHANICAL THROMBECTOMY IN A PATIENT WITH SEVERE STROKE AND SEVERE COMORBID PATHOLOGY TAKING ANTICOAGULANTS - Пеганова, Марина Анатольевна; Полукарова, Елена Алексеевна; Волкова, Александра Константиновна; Филимонов, Сергей Николаевич; Зиборова, Светлана Станиславовна; Грязнова, Елена Сергеевна; Верещагин, Максим Алексеевич (Medicine in Kuzbass, 2022)
Emergency reperfusion is the main method of treatment in the most acute period of acute cerebrovascular accident. To date, several methods of therapy are used: intravenous thrombolytic therapy, intravascular thrombectomy. The ability to choose from these methods allows you to develop an effective treatment strategy, taking into account the individual characteristics of the patient. Objective – demonstration of a clinical case of management of an aged patient with severe stroke and severe cardiac pathology while taking anticoagulants in the most acute period of stroke. Methods. A retrospective analysis of the medical history of an 82-year-old patient hospitalized in the department for the treatment of patients with stroke at the Novokuznetsk City Clinical Hospital N 1 with a diagnosis: «Cerebrovascular disease was carried out. Atherothrombotic ischemic stroke in the MCA pool on the right. Thrombotic occlusion of the ICA bifurcation with thrombus migration to the M1 segment of the right MCA». The diagnosis was verified by spiral computed tomography (SCT) of the brain and angiography of extra- and intracranial vessels. The severity of neurological deficit was assessed using the following scales: NIHSS (National Institutes of Health Stroke Scale), modified Rankin scale, Rivermead Mobility Index. Recanalization was assessed using the TICI (Treatment in Cerebral Ischemia) scale. Results. Endovascular interventions in patients with acute ischemic stroke have been carried out since September 2017 in the department for the treatment of patients with stroke at NGCH N 1 and show their high efficiency. To date, 70 patients have undergone thrombectomy. In the presented patient, the severity of the condition was due to neurological deficit (NIHSS 19 points) and concomitant cardiac pathology: coronary artery disease. PICS, parietal thrombosis of the LV apex. Paroxysmal AF, pulmonary hypertension. When choosing the method of reperfusion therapy, the clinical signs of occlusion of the main cerebral vessel and the use of anticoagulant therapy were taken into account. A decision was made to perform mechanical thrombus extraction. A day after the procedure, the neurological deficit regressed to 11 points, on the 23rd day the patient was discharged with positive dynamics, according to the NIHSS scale 6 points. The degree of functional impairment at the time of discharge was 4 points on the Rankin scale due to existing cognitive impairment. Conclusions. In the presented clinical case, the rationally chosen tactics of using modern methods of reperfusion therapy made it possible to avoid severe neurological deficit and achieve a favorable functional outcome in a patient with occlusion of the main cerebral vessel.